Vibration control of laminated composite cantilever beam operating in elevated thermal environments using fuzzy logic controller. (April 2022) - Akumalla, Ravi Kiran; Kallannavar, Vinayak; Kattimani, Subhaschandra
In the present study, vibration control of laminated composite cantilever beam operating in the elevated thermal environment is achieved using combined experimental and numerical techniques. The impact hammer test is performed on the glass-epoxy cantilever beam at different temperatures. Experimentally recorded impact hammer force signals and piezoelectric accelerometer time-domain signals are processed through a system identification toolbox in MATLAB to obtain transfer functions of the plant models. A robust fuzzy logic controller is developed to accomplish the effective vibration control of a cantilever composite beam operating at different temperatures. The fuzzy logic controller with two inputs and one output is designed using the 20 if-then rules. The results are presented in both frequency and time domain, keeping the vibration attenuation of the fundamental frequency as the point of interest. The results indicate the proposed fuzzy logic control strategy can attenuate the vibrations of a cantilever composite beam for a wide temperature range.